Characterization And Potential Utilization Of Gypsum From Lao Pdr - Panhyavisy, Sangkhone (2013)
The aim of this research work is to focus on the quality evaluation and optimization processing of the gypsum rock formed from different geological depositional setting as the potential resources for many downstream industrial applications. Samples from naturally occurring gypsum deposits were sought from two different resources in Khammouan province, and Savanakhet province, Lao PDR. These gypsum samples were subjected to detailed laboratory investigations including raw material characterization and gypsum manufacturing in order to evaluate and determined the optimized calcined gypsum powder for each gypsum resources. Based from the geological origins of these two gypsum resources, they have similar mineralogical, chemical and physical characteristic. Both resources were found to be of class I (high grade with 98% of CaSO4.2HO2), which is a specification for many industrial applications such as plaster, wallboard, cement, food and pharmaceutical, and flue gas desulphurization (FGD). However, both gypsum are not suitable for agriculture as fertilizer and paint. This proved that the quality of the end-products and its preparation were partly determined by the geological origin of the gypsum resources especially the rock mineralogy. The gypsum powder produced after crushing, grinding and calcinations at several temperatures (110 ºC, 150 ºC, 175 ºC, 200 ºC, 225 ºC & 250 ºC) were found to be in the form of CaSO4.0.5H2O (hemi anhydrate), where some water have been removed. This result is supported from the physical, chemical and mineralogical characterization on the calcined gypsum.